Exact Traveling Wave Solutions to the (2 + 1)-Dimensional Jaulent-Miodek Equation - Yongyi Gu; Bingmao Deng; Jianming Lin (Advances in Mathematical Physics)
We derive exact traveling wave solutions to the (2 + 1)-dimensional Jaulent-Miodek equation by means of the complex method, and then we illustrate our main result by some computer simulations. It has presented that the applied method is very efficient and is practically well suited for the nonlinear differential equations that arise in mathematical physics.